2002
DOI: 10.1016/s0360-3016(01)02656-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiotherapy in thymic carcinoma: treatment results and prognostic factors

Abstract: Short running head: Postoperative radiotherapy in thymic carcinomaABSTRACT Purpose: To analyze the treatment results and prognostic factors of patients with primary thymic carcinoma treated by total or subtotal tumor resection followed by radiotherapy alone. Materials and methods: From October 1987 to October 1997, twenty-six patients with thymic carcinoma were treated with complete or incomplete surgical resection and postoperative adjuvant irradiation without chemotherapy. The radiation was delivered with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 29 publications
0
36
1
1
Order By: Relevance
“…Radiation dose was found to have a significant association for local control probability in a small series consisting of 27 patients with invasive thymoma and 6 patients with thymic carcinoma [49]. However, Hsu and colleagues also found that, while Masaoka staging was a statistically significant prognostic factor, radiation dose of <60 Gy, 60 Gy, or >60 Gy was not a significant predictor of overall survival rate [48]. Ogawa and colleagues showed 100% control rates in 40 patients with thymic carcinoma who underwent complete resection and adjuvant RT with prescription doses >50 Gy [50].…”
Section: Radiotherapy For Thymic Carcinomamentioning
confidence: 95%
See 2 more Smart Citations
“…Radiation dose was found to have a significant association for local control probability in a small series consisting of 27 patients with invasive thymoma and 6 patients with thymic carcinoma [49]. However, Hsu and colleagues also found that, while Masaoka staging was a statistically significant prognostic factor, radiation dose of <60 Gy, 60 Gy, or >60 Gy was not a significant predictor of overall survival rate [48]. Ogawa and colleagues showed 100% control rates in 40 patients with thymic carcinoma who underwent complete resection and adjuvant RT with prescription doses >50 Gy [50].…”
Section: Radiotherapy For Thymic Carcinomamentioning
confidence: 95%
“…Most studies use a total dose ranging from 40 Gy to 70 Gy with daily fractions of 1.8 to 2.0 Gy. Hsu and colleagues analyzed 26 patients given adjuvant RT and show improved survival and local control with 77% 5-year survival rate, 91% 5-year local control rate, and 57% 5-year distant metastasis-free rate [48]. Radiation dose was found to have a significant association for local control probability in a small series consisting of 27 patients with invasive thymoma and 6 patients with thymic carcinoma [49].…”
Section: Radiotherapy For Thymic Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…In the Japanese series, 186 patients with thymic carcinoma were analysed with no survival difference based on post-operative treatment, regardless of the tumour stage [6]. In a more recent series of 26 patients with thymic carcinoma treated with surgery and radiotherapy, local control rate was 82% higher than that observed in a historical series [67].…”
Section: Radiotherapy Principlesmentioning
confidence: 95%
“…Timik karsinomların prognozlarının kötü olması nedeniyle hemen hemen tüm olgulara RT önerilmektedir (23). Sıklıkla 1.8-2.0 Gy fraksiyon dozlarında uygulanan 50-60 Gy RT ile olgularda %90-100 olasılıkla lokal kontrol sağlanabilmektedir (23,24). Sınırda rezektable ya da unrezektable olgular neoadjuvan KT ya da torasik RT'den fayda görebilir (25).…”
Section: Timik Karsinomunclassified